Holographic Sampling Display Based on Metagratings - Wenqiang Wan; Wen Qiao; Donglin Pu; Ruibin Li; Chinhua Wang; Yueqiang Hu; Huigao Duan; L. Jay Guo; Linsen Chen (iScience, 2020)
Summary: Glasses-free three-dimensional (3D) display is considered as a potential disruptive technology for display. The issue of visual fatigue, mainly caused by the inaccurate phase reconstruction in terms of image crosstalk, as well as vergence and accommodation conflict, is the critical obstacle that hinders the real applications of glasses-free 3D display. Here we propose a glasses-free 3D display by adopting metagratings for the pixelated phase modulation to form converged viewpoints. When the viewpoints are closely arranged, the holographic sampling 3D display can approximate a continuous light field. We demonstrate a video rate full-color 3D display prototype without visual fatigue under an LED white light illumination. The metagratings-based holographic sampling 3D display has a thin form factor and is compatible with traditional flat panel and thus has the potential to be used in portable electronics, window display, exhibition display, 3D TV, as well as tabletop display. : Optical Imaging; Optical Physics; Wave Optics; Metamaterials Subject Areas: Optical Imaging, Optical Physics, Wave Optics, Metamaterials